The Black Male Adult Learner Success Theory: unpacking institutional structures that support academic success - Goings, Ramon Bailey (Frontiers in Education, 2025)
Adult learners are one of the largest growing populations on college campuses. However, many universities do not consider this population generally and Black male adult learners specifically in policy decisions. To address this oversight there has been a growing body of work exploring the experiences of Black male adult learners in higher education, but most theories used to study this population were developed for traditional aged college students. Given the differences in the experiences of Black male adult learners, I developed the Black Male Adult Learner Success Theory (BMALST) to present an asset-based lens in which to study and make institutional decisions that cultivate the academic success of Black male adult learners. In this article I present the journey to developing the BMALST, describe the theory, and discuss how it could be used by institutions to improve the experience for Black male adult learners in higher education.